Community Structure of Spider (Araneae) in Kerandangan Nature Park, West Lombok - Hidayat, Aswangga Abigail; Artayasa, I Putu; Ilhamdi, Mohammad Liwa (Jurnal Biologi Tropis, 2026)
Kerandangan Nature Park is a conservation area with high biodiversity potential, including spiders (Ordo Araneae) which play an important role as natural predators in maintaining ecosystem balance. However, information regarding the structure of the spider community in this area is still limited. This study aims to analyze the structure of the spider community based on species composition, diversity index, evenness, and dominance in Kerandangan Nature Park, West Lombok. This study was conducted in 2025 with two replications in three management blocks, namely intensive use, limited use, and protection. Sampling was carried out using the sweep net method and pitfall traps. Data analysis used the Shannon–Wiener index (H'), evenness index (E'), and Simpson dominance index (D'). The results showed that the spider community consisted of 25 species from seven families. The community composition was dominated by Pardosa pseudoannulata (42.2%), Cytaea haematica (12.64%), and Pardosa lapidicina (8%). The diversity index (H’) ranged from 0.73 to 2.60, the evenness index (E’) from 0.19 to 0.85, and the dominance index (D’) from 0.084 to 0.68. The conclusion is that the spider community structure is in the moderate and relatively stable category, thus supporting ecosystem balance in the area.